2012
DOI: 10.3174/ajnr.a3207
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Flow Diversion for Paraclinoid Aneurysms: A Matched-Pair Analysis Compared with Standard Endovascular Approaches

Abstract: Flow diverters achieve a much higher rate of complete angiographic obliteration compared with other standard endovascular techniques in the treatment of internal carotid artery aneurysms. In this series, this higher angiographic obliteration rate did not occur at the expense of an increased rate of complications. Careful long-term follow-up is of the utmost importance to definitively validate flow diversion as a superior therapeutic strategy for proximal internal carotid artery aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 23 publications
(25 reference statements)
2
49
0
Order By: Relevance
“…6,11,12 Lanzino et al 13 reported a significantly higher rate of complete occlusion in patients with the PED (76%) than in patients (21%) treated with coils with a similar rate of morbidity. Likewise, Chalouhi et al 2 compared the safety and efficacy of the 2 techniques in unruptured, large, and giant (Ն10 mm) aneurysms, reporting a similar complication rate (7.5%) and a higher aneurysm occlusion rate (86% versus 41%) with flow diversion.…”
Section: Discussionmentioning
confidence: 99%
“…6,11,12 Lanzino et al 13 reported a significantly higher rate of complete occlusion in patients with the PED (76%) than in patients (21%) treated with coils with a similar rate of morbidity. Likewise, Chalouhi et al 2 compared the safety and efficacy of the 2 techniques in unruptured, large, and giant (Ն10 mm) aneurysms, reporting a similar complication rate (7.5%) and a higher aneurysm occlusion rate (86% versus 41%) with flow diversion.…”
Section: Discussionmentioning
confidence: 99%
“…Paraclinoid aneurysms are increasingly being treated with flow-diversion stents, which may further reduce the procedural risks associated with endovascular treatment. [22][23][24][25] Angiographic and clinical outcomes from previous studies are summarized in Table 7. The immediate complete occlusion rate in our series was low (9.5%) compared with those in earlier studies (28.2%-86.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular treatment can consist of ICA balloon occlusion, selective coiling with or without balloon or stent assistance, or parent ICA reconstruction with flow diverters. [6][7][8][9] At the Sint Elisabeth Ziekenhuis, therapeutic ICA occlusion has been the preferred treatment for large and giant ICA aneurysms since 1995, despite the availability in the last decade of new endovascular devices, such as stents and flow diverters, intended to spare the parent ICA. We report the clinical and imaging results of ICA occlusion for aneurysms in a large single-center patient cohort.…”
mentioning
confidence: 99%